Neuroprotective Effects of the Asparagus racemosus Root Extract on Ovariectomized Rats - Lalert, Laddawan; Kruevaisayawan, Hathairat; Amatyakul, Patcharada; Khongsombat, Onrawee (Journal of Physiological and Biomedical Sciences, 2013)
Estrogen decline in menopausal women may impair the cognitive function. This change can be ameliorated by estrogen replacement therapy (ERT). However, ERT is often overshadowed by the serious side effects of estrogen use in menopause women. Asparagus racemosus (AR) is well known for its phytoestrogenic properties while neuroprotective effects of AR in ovariectomized model are unknown. This study aimed to investigate effects of AR root extract on serum estradiol level, learning and memory, and neuronal viability in hippocampus and medial prefrontal cortex (mPFC) of ovariectomized rats by using electrochemiluminescence immunoassay, the novel object recognition test and histological analysis, respectively. Adult female Wistar rats were divided into five groups and gavaged for 90 days with vehicle (propylene glycol) for sham and OVX groups and another 3 groups of OVX rat were gavaged with 100 or 1000 mg/kg B.W./day of AR root extract or 0.1 mg/kg B.W./day of 17α-ethynylestradiol (EE), respectively. There was a significant decrease in recognition index of the OVX rats and AR root extract could reverse this effect. The serum estradiol level was significantly decreased in OVX group whereas AR root extract did not statistically change from that demonstrated by OVX group. The OVX rats showed a marked decrease in the number of neurons in hippocampus and mPFC. AR root extract and EE could reduce the neuronal loss in hippocampus and mPFC. The results obtained suggest that AR could improve cognitive ability in ovariectomized model which associated with increase neuronal viability of hippocampus and mPFC. AR may be a beneficial agent for preventing cognitive decline induced by ovariectomy.